Pengaruh Budaya Toraja Ma’nene’ Terhadap Identitas Sosial Masyarakat di Dusun Malombu Kecamatan Awan Rantekarua Kabupaten Toraja Utara - Kesya Payungallo; Muh Said; Shasliani Shasliani (Jambura History and Culture Journal, 2026)
This study aims to find out: 1) The description of Toraja ma'nene' culture in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency, 2) The description of the social identity of the community in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency, and 3) The influence of Toraja ma'nene' culture on the social identity of the community in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency. This study uses a quantitative approach with a type of quantitative descriptive research. The research variables consisted of ma'nene' (variable X) and social identity (variable Y). Data collection techniques use observation, questionnaires and documentation. Meanwhile, the analysis techniques used are descriptive statistical analysis and inferential statistical analysis using the help of SPSS 26. The results of the study showed that: 1) The description of Toraja ma'nene' culture in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency was in the "very high" category with indicators of (a) community participation (b) community knowledge (c) community perception. 2. Overview of Social Identity The community in Malombu Hamlet, Awan Rantekarua District, North Toraja Regency is in the "very high" category with indicators of (a) cultural pride, (b) social relations, (c) cultural values. 3) There is a positive and significant influence between the Toraja ma'nene' culture on the social identity of the community in Malombu Hamlet, Awan Rantekarua District, Toraja Regency with a significant value of correlation coefficient of 0.680.